HIV/AIDS Counselling, Just a Phone Call Away : Four Case Studies of Telephone Hotline/Helpline Projects. - UNAIDS (UNAIDS best practice collection HIV/AIDS counselling, just a phone call away, 2003)
Around the world, telephone helplines have proved to be an accessible, affordable and acceptable source of HIV/AIDS information, counselling and referrals for callers from all walks of life. First initiated in high-income countries, helplines have expanded into many low- and middle-income countries, particularly as the latter improve their telecommunications infrastructure and identify HIV/AIDS as a pressing social concern. This Best Practice Case Study offers an opportunity to learn from the experiences of well-established helplines in India, the Philippines, South Africa, and Trinidad and To.